Cambodia : Toward Performance-Based Civil Service - World Bank (World Bank, Phnom Penh, 2020)
Government accountability has become a global moral imperative. Governments over the world aim to continuously improve public service delivery, transparency, and accountability to respond to citizens’ needs. Cambodia became a lower-middle-income country (LMIC) in 2015 and the task of delivering public services continues to become more complex, highlighting the need for public administration reform (PAR). The Royal Government of Cambodia recognizes a link between the quality of governing institutions and economic growth and places reform of governance institutions at the core of its rectangular strategy phase fourth (2018-2023). The strategy aims for higher levels of income and standards of living, which can lead to transformative changes such as the emergence of a middle class, increased urbanization, and greater integration with the outside world. The policy note adopts the government production function model as a way to understand the government’s capability in converting policies to outcomes, which in turn involves two interrelated drivers: quality of bureaucracy and the efficiency of frontline activities in service delivery, infrastructure provision, and revenue collection. Also included are the experiences of relevant countries as well as conceptual models and ideas that can be useful to suggest reference points for further reforms. It makes recommendations across five core areas to deepen public administration reform: strengthening the quality and effectiveness of public service delivery; optimizing organizational structures; improving management and development of contemporary approaches to human resources; reforming pay and allowances; and improving data needed for improved decision making.